Uterine sutures at prior caesarean section and placenta accreta in subsequent pregnancy: a case–control study. (26th March 2014) - Sumigama, S; Sugiyama, C; Kotani, T; Hayakawa, H; Inoue, A; Mano, Y; Tsuda, H; Furuhashi, M; Yamamuro, O; Kinoshita, Y; Okamoto, T; Nakamura, H; et al.
<x xml:space="preserve">Abstract</x> Objective To clarify the effects of uterine myometrial suture techniques at prior caesarean section on the incidence of pathologically diagnosed placenta accreta in placenta praevia with prior caesarean section (PPPC). Design Case–control study. Setting Eleven tertiary referral hospitals in central Japan. Population A total of 98 cases of placenta praevia, a history of one or more prior caesarean sections, and a history of uterine transverse incision and usage of only absorbable thread for myometrial sutures at the prior caesarean section. Exclusions were a history of myomectomy or Strassmann's operation. Methods Cases were grouped into a pathologically diagnosed placenta accreta group (38 cases) and a no accreta group (60 cases). Clinical characteristics including uterine suture methods at prior caesarean section were compared (single‐layer versus double‐layer closure; continuous versus interrupted sutures in the inner myometrial layer). Main outcome measure The incidence of placenta accreta. Results No difference was found comparing single‐layer with double‐layer closure in the incidence of placenta accreta (37.1 versus 39.7%, P = 0.805); however, a significant difference was found comparing continuous with interrupted sutures (58.1 versus 29.9%, P = 0.008). Multivariable logistic regression analysis with stepwise selection for the eight factors meeting the criterion of P < 0.10 in univariate analysis was used, and four independent factors were selected, as follows: gravidity ≥ 3 (adjusted odds ratio, aOR, 3.4, 95% confidence interval, 95% CI, 0.99–11.6, P = 0.050); total praevia (versus non‐total, aOR 18.4, 95% CI 3.2–107.0, P = 0.001); anterior/centre placenta (versus posterior, aOR 16.4, 95% CI 3.7–72.2, P < 0.001); and continuous sutures (versus interrupted, aOR 6.0, 95% CI 1.4–25.2, P = 0.015). Conclusions In this limited study, a history of continuous sutures on the inner side of the uterine wall showed potential to influence the development of placenta accreta in PPPC patients.